PERANCANGAN ALGORITMA DAN PEMROGRAMAN KOMPUTER DALAM BAHASA TURBO BASIC DAN PASCAL UNTUK MEMPREDIKSI TINGKAT KELANGSUNGAN HIDUP (GOING CONCERN) PERUSAHAAN DENGAN PARAMETER ALTMAN Z-SCORE - Yudha Herlambang (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
As we know that,the aspect of going concern or bankruptcy of the entitiy become the issued or the problem must be considered by the external auditor.In the profession of Public Acccountant.external auditor must give the opinion objectively and independent. So that the Report of AuditorIndependent give the objective and right information ( no biased information) to the external user of Financial Statement how to make decision. One of the judgement must be considered by the external auditor is the bancruptcy of the entity (auditee ).One of the alternative method to decide the condition of entity’s going concern is Altman Z Score. In this paper,author will discuss about designing the Programming Algorithm of Altman - Z Score. The author design the program mentioned above by using Quick Basic Programming Language and Pascal Software.The author also design the accounting ratio programming into the part of source code or listing program mentioned above